(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Il rilievo “esemplare” (ma contenuto) di un istituto nuovo e peculiare - 2. Un bilancio ancora parziale e limitato - 3. Uno sguardo generale sulla situazione mondiale: motivi di soddisfazione - 4. Un uso ragionevole del rito breviore - 5. La “non scontata” soluzione del giudizio episcopale - 6. La “relativa” controtendenza statunitense - 7. La focalizzazione su alcune situazioni particolari: motivi di preoccupazione - 8. Un’adozione territorialmente molto sbilanciata - 9. La renitenza di alcuni episcopati - 10. L’anomalia sudamericana e africana - 11. L’impressione di un’applicazione troppo diversificata e disomogenea - 12. Il riscontro estensivo o applicativo - 13. Il riscontro intensivo o procedimentale - 14. Trend e prospettive di sviluppo. The Course of the Statistical Data regarding the ‘Processus Matrimonialis Brevior coram Episcopo’: Motives for Contentment and Some Preoccupations ABSTRACT: The article analyzes the course of the statistical data on the abbreviated matrimonial process before the bishop. Although the data is still uncertain and limited (since it covers the period 2016-2019 and only certain targeted statistical points), it is possible to generally acknowledge that the practice is fairly restrained and reasonable. Regardless of the fact that the appeals were very rare, the admission to the processus brevior does not seem to denote a definitive institutional solution (the emergence of a number of cases in which the matter was referred to the ordinary method). Even in the United States, a representative country regarding the ecclesiastic judicial activity and problems with regard to said activity, the number of the briefer processes seems to be fairly moderate. Since the briefer process represents a special type of process, the cautious and thought-out reception of this institute points to a certain maturity of the system. The data show some reserves regarding the adoption of this institute in some territories, as well as the resistance of certain bishops, together with certain anomalies in its development in South America and Africa. The impression upon analyzing the data is that the enforcement of the institute is still too diversified and that it lacks homogeneity, either in its territorial extension or with regard to the intensity of the enforcement of the institute. The author then perceives the need for a greater extent of directive interventions and authoritative instructions, while he outlines certain trends and prospects for development.